2000
DOI: 10.2527/2000.7851149x
|View full text |Cite
|
Sign up to set email alerts
|

Duration of the seasonal anestrus in sheep selected for fertility in a fall-lambing system.

Abstract: Crossbred ewes (1/2 Dorset, 1/4 Rambouillet, and 1/4 Finnsheep) from a flock being selected for spring fertility, defined as ability to lamb following ram exposure in May and June in Virginia (37 degrees N latitude), were used to study the duration of the seasonal anestrus. In the first 3 yr of the study (1992, 1993, and 1995), mature ewes were divergently selected based on EBV for fertility, and the duration of anestrus was measured by continuously exposing the ewes to vasectomized rams equipped with marking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 16 publications
1
18
0
1
Order By: Relevance
“…In addition, the ability of the March-lambing, lactating ewes to deliver fully developed lambs at term was compromised. Levels of fertility achieved by spring-bred lactating OOS ewes in this study appear to be unprecedented for temperate sheep breeds, and are consistent with results of Vincent et al (2000), Notter et al (2011) and Goff et al (2013) demonstrating that selection for fertility in May and June has extended the breeding season until at least early summer. The OOS ewes were more likely to mate and establish pregnancy during lactation than St. Croix ewes, but these advantages were negated by their lower ability to maintain those pregnancies.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…In addition, the ability of the March-lambing, lactating ewes to deliver fully developed lambs at term was compromised. Levels of fertility achieved by spring-bred lactating OOS ewes in this study appear to be unprecedented for temperate sheep breeds, and are consistent with results of Vincent et al (2000), Notter et al (2011) and Goff et al (2013) demonstrating that selection for fertility in May and June has extended the breeding season until at least early summer. The OOS ewes were more likely to mate and establish pregnancy during lactation than St. Croix ewes, but these advantages were negated by their lower ability to maintain those pregnancies.…”
Section: Discussionsupporting
confidence: 72%
“…Attempts to breed lactating ewes in spring have consistently been disappointing (Bourke, 1964;Whiteman et al, 1972;Cognie et al, 1975;Pope et al, 1989), and use of hormone or light manipulation to improve spring fertility has generally not been successful in lactating ewes (Restall et al, 1978;de Nicolo et al, 2006;Martemucci and D'Alessandro, 2010). Selection to improve ewe fertility in a crossbred (50% Dorset, 25% Rambouillet, 25% Finnish Landrace) sheep population mated in May and June at Virginia Tech (37°N latitude) resulted in significant selection response (Notter and Cockett, 2005) and correlated increase in duration of the breeding season (Vincent et al, 2000;Notter et al, 2011;Goff et al, 2013). However, fertility of ewes from this out-of-season breeding (OOS) line has not been evaluated during lactation.…”
Section: Introductionmentioning
confidence: 99%
“…In ewes evaluated in 1992, 1993, and 1995, the seasonal anestrus of high-fertility ewes from the S and E lines (mean EBV of 12.6%) averaged only 28.4 d and was significantly shorter than the 70.1 d of anestrus observed in low-fertility ewes (mean EBV of 0.3%). Vincent et al [46] further reported that 13 OOS ewes evaluated in 1997 all exhibited nearly continuous cyclicity during spring and summer, with a mean period of anestrus of only 11.3 d.…”
Section: Characterization Of Oos Ewesmentioning
confidence: 99%
“…mid-January through the following July and monitoring their mating behavior [46]. Only ewes that had lambed in the previous autumn (October and November) were used to ensure physiological comparability, and the same rams were used throughout the study to avoid possible induction of ram effect by introduction of novel males.…”
Section: Characterization Of Oos Ewesmentioning
confidence: 99%
“…The genetic basis of OOS kidding has not previously been explored in depth in dairy goats, however, several studies in sheep have found a genetic component to traits related to seasonality (Quirke et al, 1986;Chemineau et al, 2010), and selection for fall lambing has been achieved (Vincent et al, 2000). Smith et al (1992) estimated a heritability of 0.23 for seasonal breeding ability, based on a binary trait of successful/unsuccessful breeding in the late spring/summer months.…”
Section: Out Of Season Breedingmentioning
confidence: 99%